Culpabilidade: o cargo público de elevada responsabilidade e sua conversão em hipótese de elevação da pena-base - ASSIS, Carlos Eduardo Silva (2022)
This article has as primary purpose analyze the "public office with high responsibility" category, which is jurisprudentially used as factual element that denotes "intense culpability" in the base-penalty’s fixation process. The study of the topic proves to be relevant, since the erroneous conversion of this category into a moral hypothesis of raising the base-penalty causes damages to the defendant, violating the principles of legality and ne bis in idem, in addition establishes a random relationship between the administrative responsibility, inherent to the public office held by the defendant, and the criminal responsibility, with repercussions on the censorship grade of the conduct when filling the meaning of culpability present in article 59 of the Brazilian Penal Code (CPB). The study characterizes itself as a bibliographic research, of qualitative nature and it was produced from the analysis of three different judicial decisions, which uses the thesis of the high responsibility public position as denoter of intense reprobability of the criminal conduct, in the passive corruption crimes.